Agent and multi-agent systems : technology and applications : 11th KES International Conference, KES-AMSTA 2017 Vilamoura, Algarve, Portugal, June 2017 Proceedings - Jezic, Gordan; Kusek, Mario; Chen-Burger, Yun-Heh; Howlett, Robert J., 1954-; Jain, L. C. (Springer, 2017)
This volume highlights new trends and challenges in research on agents and the new digital and knowledge economy, and includes 23 papers classified into the following categories: business process management, agent-based modeling and simulation, and anthropic-oriented computing. All papers were originally presented at the 11th International KES Conference on Agents and Multi-Agent Systems - Technologies and Applications (KES-AMSTA 2017) held June 21-23, 2017 in Vilamoura, Algarve, Portugal. Today's economy is driven by technologies and knowledge. Digital technologies can free, shift and multiply choices, and often intrude on the territory of other industries by providing new ways of conducting business operations and creating value for customers and companies. The topics covered in this volume include software agents, multi-agent systems, agent modeling, mobile and cloud computing, big data analysis, business intelligence, artificial intelligence, social systems, computer embedded systems and nature inspired manufacturing, etc., all of which contribute to the modern Digital Economy. The results presented here will be of theoretical and practical value to researchers and industrial practitioners working in the fields of artificial intelligence, collective computational intelligence, innovative business models, the new digital and knowledge economy and, in particular, agent and multi-agent systems, technologies, tools and applications.
International conference proceedings.
Includes author index.
Keywords: Intelligent agents (Computer software) -- Congresses.; Distributed artificial intelligence -- Congresses.; elektronické knihy; electronic books